Changes in Plate Motions Caused by Increases in Gravitational Potential Energy of Mountain Belts. (10th October 2022) - England, Philip; Molnar, Peter
Abstract: Reconstructions of motions of the Nazca, South American, and Indian plates record short‐duration (≲10 Myr) variations in angular velocity, which enable a vector‐based test of the hypothesis that mountain uplift can cause changes in plate motion. Reductions in velocity of Nazca and South America between ∼12 and 6 Ma coincide with a phase of rapid surface uplift in the Central Andes. Decrease in the rate of India's convergence with Eurasia between ∼20 and 10 Ma corresponds to an increase in gravitational potential energy per unit area (GPE) within Tibet, marked by a transition from crustal thickening to thinning. The vectorial test shows that, in each case, the only change in driving force capable of balancing the change in basal drag is an increased resistance along the convergent boundary to the plate. Changes in GPE associated with mountain uplift provide a calibration for basal drags on plates. Basal tractions of ∼0.1–1 MPa provide resisting forces comparable in magnitude to driving forces from GPE variation in ocean lithosphere. The rapid change in motion of the Indian plate between about 48 and 41 Ma is explained by the juxtaposition of the Indian continent against the Andean‐type margin of the Transhimalaya and reduction in driving force due to loss of the slab. The net slab driving force lost was ∼2–4 TN m −1, in agreement with previous studies suggesting that forces resisting slabs' penetration into the mantle largely offset their negative buoyancy. Key Points: Calculation of forces required to cause rapid changes in plate motion test the hypothesis that some stem from increase in gravitational potential energy (GPE) of mountains Rapid decreases in velocity of Nazca, South American, and Indian plates require increases in resistance at their convergent boundaries Geological evidence shows that the Miocene decreases in velocity were contemporaneous with increases in GPE of the Andes and Tibet